Rapid quantitative D‐dimer to exclude pulmonary embolism: a prospective cohort management study. (5th February 2016) - Bates, S. M.; Takach Lapner, S.; Douketis, J. D.; Kearon, C.; Julian, J.; Parpia, S.; Schulman, S.; Weitz, J. I.; Linkins, L. A.; Crowther, M.; Lim, W.; Spencer, F. A.; et al.
Abstract : Essentials It is not known ifD ‐dimer testing alone can safely exclude pulmonary embolism (PE). We studied the safety of using a quantitative latex agglutinationD ‐dimer to exclude PE in 808 patients. 52% of patients with suspected PE had a negativeD ‐dimer test and were followed for 3 months. The negative predictive value ofD ‐dimer testing alone was 99.8%, suggesting it may safely exclude PE. Summary: Background: Strategies are needed to exclude pulmonary embolism (PE) efficiently without the need for imaging tests. Although validated rules for clinical probability assessment can be combined withd ‐dimer testing to safely exclude PE, the rules can be complicated or partially subjective, which limits their use. Objectives: To determine if PE can be safely excluded in patients with a negativeD ‐dimer without incorporating clinical probability assessment. Patients/Methods: We enrolled consecutive outpatients and inpatients with suspected PE from four tertiary care hospitals. All patients underwentD ‐dimer testing using the MDAD ‐dimer test, a quantitative latex agglutination assay. PE was excluded in patients with aD ‐dimer less than 750 μg FEU L −1 without further testing. Patients withD ‐dimer levels of 750 μg FEU L −1 or higher underwent standardized imaging tests for PE. All patients in whom PE was excluded had anticoagulant therapy withheld and were followed for 3 months for venous thromboembolism (VTE). Suspected events during follow‐up were adjudicated centrally. Results: Eight hundred and eight patients were enrolled, of whom 99 (12%) were diagnosed with VTE at presentation. Four hundred and twenty (52%) patients had a negativeD ‐dimer level at presentation and were not treated with anticoagulants; of these, one had VTE during follow‐up. The negative predictive value ofD ‐dimer testing for PE was 99.8% (95% confidence interval, 98.7–99.9%). Conclusions: A negative latex agglutinationD ‐dimer assay is seen in about one‐half of patients with suspected PE and reliably excludes PE as a stand‐alone test.